Wellness Tourism as a Pathway to Sustainable Tourism: Opportunities and Challenges in Lombok, West Nusa Tenggara - Suryantari, Yulita; Lanisy, Nihan Anindyaputra; Ngarbingan, Hubertina Karolina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
Wellness tourism is one of the increasingly popular forms of tourism that holds significant potential to support sustainable tourism development. This research was conducted in Lombok, West Nusa Tenggara, known for its natural beauty, rich culture, and serene, pollution-free atmosphere, which are key factors supporting health and relaxation-based tourism. The study aims to explore the potential and challenges of developing wellness tourism in Lombok and its contribution to sustainable tourism in the region. Using a descriptive qualitative method, data was collected through observation, interviews with tourism stakeholders and tourists, as well as field documentation. The findings indicate that Lombok, particularly the Gili Trawangan and Senggigi areas, has strong appeal as a wellness tourism destination. However, the development of wellness tourism still faces several challenges, such as a lack of targeted promotion and high domestic transportation costs. These findings suggest that wellness tourism can be a strategic approach to achieving sustainable tourism, provided there is policy support, adequate infrastructure, and active involvement of local communities.